Sistem Kendali Pembubuhan Alumunium Sulfat Menggunakan PLC Schneider Tm221 Pada Dosing Station di PT Kraktau Tirta Industri - Muamar Ilham Zaini; Desmira Desmira (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2025)
The aluminum sulfate (alum) affixing control system is an important aspect of the water treatment process at PT Krakatau Tirta Industri. This research discusses the implementation of the Schneider TM221 Programmable Logic Controller (PLC) as a control system at a dosing station to automate the alum affixing process precisely and efficiently. The aim of using this PLC is to increase dosage accuracy, improve water quality, and minimize waste of chemicals. In this system, the Schneider TM221 PLC is used to regulate the flow of chemicals based on predetermined parameters, such as the level of water requirements and the required alum concentration. . The designed control system includes integration between flow sensors, pumps and Human Machine Interface (HMI) devices to monitor processes in real-time and provide automatic responses to changes in operational conditions. The research results show that the use of the Schneider TM221 PLC is able to increase the efficiency of the alum affixing process compared to manual or semi-automatic methods. This system also reduces operational errors, increases process stability, and provides better diagnostic and maintenance capabilities. Thus, the application of the Schneider TM221 PLC at the dosing station at PT Krakatau Tirta Industri contributes significantly to improving the quality of water treatment process control